Induction of neuronal phenotypes from NG2+ glial progenitors by inhibiting epidermal growth factor receptor in mouse spinal cord injury - Ju, Peijun (2013)
Besides neural stem cells, some glial cells, such as GFAP+ cells, radial glia, and oligodendrocyte progenitor cells can produce neuronal cells. Attractively, NG2+ glial progenitors exhibit lineage plasticity, and they rapidly proliferate and differentiate in response to central nervous system (CNS) injuries. These attributes of NG2+ glial progenitors make them a promising source of neurons. However, the potential of neuronal regeneration from NG2+ glial progenitors in CNS pathologies remains to be investigated. In this study, we showed that antagonizing epidermal growth factor receptor (EGFR) function with EGFR inhibitor caused a significant number of proliferative NG2+ glial progenitors to acquire neuronal phenotypes in contusive spinal cord injury (SCI), which presumably led to an accumulation of newly generated neurons and contributed to the improved neural behavioral performance of animals. In addition, the neuronal differentiation of glial progenitors induced by EGFR inhibitor was further confirmed with two different cell lines either in vitro or through ex vivo transplantation experiment. The inhibition of EGFR signaling pathway under the gliogenic conditions could induce these cells to acquire neuronal phenotypes. Furthermore, we find that the Ras-ERK axis played a key role in neuronal differentiation of NG2+ glial progenitors upon EGFR inhibition. Taken together, our studies suggest that the EGFR inhibitor could promote neurogenesis post SCI, mainly from the NG2+ glial progenitors. These findings support the possibility of evoking endogenous neuronal replacement from NG2+ glial progenitors and suggest that EGFR inhibition may be beneficial to CNS trauma.